Evaluation of World University Rankings of Southeast Asia HEIs Image - Muhammad Izharuddin; Faizal Susilo Hadi; Meirza Cahya Lestyorini (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Today's world university rankings have gained prominence in tandem with internationalization endeavors. However, the impact of empirical rankings on the HEI brand image has yet to be thoroughly explored. This research aims to assess the impact of university rankings, based on universal standards and comparable metrics, on brand image at local, national, regional, and international levels. Using data from SciVal and QS World University, we analyzed 47 HEIs in Southeast Asia over ten years through panel data regression. The results shows that HEI rankings affect the brand image of the international media, regional media, national media, and local media. Awards received and mass media in general also got impacted by HEI global ranking. It expands the literature on higher education, providing ranking readings on multi-level reputation articulations. World university rankings can be used as a strategy to increase regional reputation in Southeast Asia as well as internationally. Future research could broaden the scope of regional data and use various types of world university rankings. In addition, other impacts, such as international students, inbound and outbound faculty, joint research, and other international indicators, can be further investigated.